Practices and Challenges of Professional Learning Communities: A Mixed Method Study on Social Sciences Faculty of Government Colleges in Bangladesh - Muhammad Jakir Al-Faruki; Md. Sajedur Rahman (Journal of Educational Sciences, 2022)
The study is intended to investigate the nature and challenges of PLC in government colleges of Bangladesh by applying mix method approach. The investigation is conducted principally based on primary data in collaboration with some sort of secondary sources of data which make the study more consequential. Accordingly, to conclude the finding it triangulates the quantitative analysis, qualitative information and researchers’ observation. Consequentially, the inference drawn from the investigation implicates that there is no programmed PLC practices exist in Bangladeshi college education as CPD activities. In addition, there is some factual and potential challenges exist to implement PLC related to institutional reality and personality trait that is motivational in nature. The motivational aspect of professional is also engendered by institutional practices. Finally, to find out the challenges the study also has drawn some recommendations for resolution of the identified challenges.